Trends and Visualization of Website-Based Physics Learning: A Bibliometric Analysis from 2002 to 2023 - Laeli, Silvia; Jumadi, Jumadi; Kuswanto, Heru; Wulandari, Novita (FKIP Universitas Lampung, 2024)
Websites are now widely accessible across all disciplines. The aim of this study is to analyze the comparative trends in research on the 100 most cited website-based learning publications across all fields, to identify comparative visualizations of trend mapping in website-based learning publications in physics education research, and to determine the countries that have published the most website-based learning research from 2002 to 2023. This study conducts a bibliometric analysis using the keywords 'website-based learning' as a general field and 'website-based physics' to specifically investigate the implementation of websites in physics education. The metadata collected is sourced from the Scopus database and analyzed and visualized using VOSviewer and datawrapper. This research shows that the research trend in website-based learning across all fields is increasing annually. The main keywords used in website-based physics learning research are 'Websites', 'Learning systems', and 'Artificial intelligence' with a total link strength of 23, 16, and 14, respectively. Keywords: website, bilbliometric, physics learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1165-1182